Ekspresi HSP 70 dan Ekspresi Reseptor Opioid Mu pada Penurunan Nyeri Terapi Bekam Basah - Imam Subadi; Hening Laswati; Harjanto JM (Universitas Airlangga, 2016)
Introduction: Wet cupping therapy widely used to reduce the pain, but the mechanisms of pain reduction on wet cuppig therapy is unclear. Stretching and punctures on wet cupping therapy cause stress on the cell. Cells that are stressed express HSP 70 and mu opioid receptors. This study aims to prove the correlation increased expression of HSP 70 and an increase in post-mu opioid receptor wet cupping therapy.Methods: The study is an experimental research design with randomized control group post-test only design. Twenty-four rats type Wistar (Rattus norvegicus) were randomly divided into three groups, each consisting of eight mice are negative control group (normal mice), group induction of pain with Complete Freund's Adjuvant (CFA) alone (positive control) and group by induction of pain and bekam basah therapy (10 puncture and negative pressure: - 200 mmHg, 5 minutes). Samples were taken from the skin and immunohistochemical examination with the monoclonal antibody anti mu opioid receptors. The reaction time pain threshold measured using a hot-plate. Data were analyzed by oneway ANOVA and Pearson Correlation using SPSS version 17.Results: This study shows that there is an increased expression of HSP 70 (P <0.05) compared to the positive control group (p <0.05) and increased expression of mu opioid receptors ( p <0.05) compared to the positive control group (p <0.05). There is an increased pain threshold reaction time (p <0.05) compared to the positive controls (11.78 ± 3.56). There is a correlation between an increased expression of HSP 70 and an increase in mu opioid receptor (β = 0893; p = 0.000) and there was a correlation between the increase in mu opioid receptor with a reaction time of pain threshold (β = 0713; p = 0.002).Discussion: Wet cupping therapy increase HSP 70 expression, opioid mu receptor, and decrease pain level.